(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This study investigates the impact of a proposal for applying Content and Language Integrated Learning (CLIL) approach for teaching chemistry on seventh graders in a private school, in which we as language teachers, not only teach language, but also, we must teach other subject areas as chemistry. The study aims to assess the effectiveness of the CLIL approach in enhancing students’ comprehension of both chemistry concepts and English language skills. The research is motivated by improving students’ needs in English as a foreign language. The objectives include design and apply fundamental principles of CLIL in chemistry class through the designing and application of a module or didactic unit about periodic table of elements in chemistry class. The following research questions are considered for this study; how does the implementation of CLIL affect students’ understanding of the periodic table of the elements in chemistry class? And how does CLIL influence students’ engagement and motivation in learning in chemistry class? The methodology used is action research, class observation notes and entry tests were considered for diagnosed students’ language needs. It highlights the importance of improving technical vocabulary, the level of reading comprehension, as well as problems in sentence construction and overcoming difficulties in connecting ideas. Additionally, the study delves into the CLIL approach, emphasizing its role in promoting language learning, intercultural skills, and a deeper understanding of subject matter.